Fostering AI literacy in pre-service teachers: impact of a training intervention on awareness, attitude and trust in AI - Bilbao-Eraña, Ainara; Arroyo-Sagasta, Amaia (Frontiers in Education, 2025)
The proliferation of generative artificial intelligence (AI) tools in recent years has transformed the educational landscape. This evolution has increased the need to train teachers to adapt to a context in which this technology is ubiquitous, and to prepare their future students for it. However, the effectiveness of AI training programmes for teachers has not been widely analysed. AI literacy has a positive influence on attitudes and perceptions toward technology. It also improves understanding of the role of technology in everyday life, facilitating the conscious and critical integration of AI, including in educational contexts. In this context, the lack of qualified AI teachers is one of the most significant obstacles to integrating the technology itself into basic education itself. This study evaluates the effect of an AI literacy-based intervention on improving the perceptions of AI among pre-service teachers. To carry out the analysis, the pre-service teachers’ perceptions were evaluated using the PAICE questionnaire, which measures awareness, attitude, and trust in AI, before and after the training session. Paired-sample t-tests revealed significant improvements in awareness and attitude. Trust increased numerically but did not reach statistical significance. These results suggest that concise, concept-driven instruction can influence awareness and attitude toward AI. In line with these results, a comparison with the findings of a larger study highlights that self-assessed knowledge about AI is notably higher in the group of pre-service teachers involved in the intervention. The study contributes to the integrative design of training programmes for pre-service and in-service teachers, combining conceptual, ethical, and experiential components. It also highlights the need to promote teacher development in order to enable them to respond critically and consciously to an educational system that has been radically transformed by AI.